The possibilities of symbolic language employment in children consultation and psychotherapy - Būtienė, Diana (Psichologija, 2004)
The article presents a case of psychotherapeutic work with a 7-year-old girl. The origin of the symptoms, their sense and therapeutic result are analysed in order to look at the child’s world of fantasies while comparing the approaches of different psychotherapeutic schools such as dynamical, analytical, individual psychology and existential. According to the psychodynamical theory the girl’s present difficulties can be cosidered to be the reflection of unsolved problems in the previous stages of development which were caused by some urgent events of life. The essence of the problems is a confflict between Id and Superego which reveals itself by inability to tolerate one’s own agressive impulses and express them in a constructive way. Somatic disorders and the fear of death are the expression of autoagression. The symbolics of drawings can be interpreted as gradual understanding of one’s agression, accepting it and being able to control the process. As maintained by A. Adler’s individual psychology, the girl’s “perfect” lifestyle was determined by the aspiration of recognition when the aim is to raise oneself rather than cooperate. The disorders were brought about by the inadequacy between ambitions and real relations. The fear of death can be understood as the expression of the “good girl’s” unsuccessful lifestyle with its fictitious aims. The heroes’ stories in the drawings can be viewed as transition from well adapted social behaviour to social interest, from raising oneself to cooperation. On the authority of C. G. Jung’s analytical theory, the girl’s intrapsychic structure is dominated by Person’s archetipe while the Child’s and Self’s archetypes were not as strongly expressed. This disbalanse, inequivalent relation between the stuctures of consciousness and subconsciousness were the inner causes which brought about these disorders. The fear of death and somatic disorders mean experiencing impasse (one of the stages of transformation), when a person gives up his previous awareness and loses the feeling of his own self. The heroes described and the stories created are the expression of the personality’s transformation process in the course of which other relations of Self and Ego were formed which were different in quality. As claimed by the existential theory, the fear of death is related to the fear of authentic life. The less a man’s life is filled with personal purports the stronger is the fear of death. The completion of life is inevitability. One can encounter this fact at any age and it is always followed by disturbing happenings. Such experience changes the feeling of one’s own self, his inner psychological world and personal relations. This can be the basis of finding oneself which causes growing, renovation of vitality and creativity in daily routine. The girl’s therapeutic story can be treated as her search for authenticity and possibilities to create her own life and her refusal to be just a passive onlooker. Whatever school the psychotherapeutist or consultant represents, the most important thing is the quality of the contact between the child and the therapeutist. Its essence lies in understanding the other person. It is a kind of relationship which enables the child to move away from identification with his parents, to have the feeling of being really seen, having relation. It is the moment of revealing oneself, which is only possible in contact with another person, when frankness is mutual. Consequently, the child obtains a new understanding of relations which enables therapeutic changes. The effect of human relations can be understood as a new different empiric process which becomes powerful due to the genuineness of relations.